Ecological and parasitological characteristics of the “Fasciola hepatica L.–Lymnaea (Galba) subangulata” system - Zhytova, O. P.; Shelyuk, Yu. V.; Andreeva, O. Yu; Lehka, A. S. (Bìologìčnì studìï, 2022)
Background. Fasciolosis is one of the most common zoonoses in the world, caused by the trematode Fasciola hepatica L. This helminthiasis leads to significant economic damage in animal husbandry and can pose a direct threat to human health. Today, in the context of climate change, detailed knowledge of the biological characteristics of the trematode F. hepatica circulation will make it possible to predict outbreaks of fasciolosis on farms in detail and plan effective measures to combat this dangerous disease. The purpose of this work is to clarify some aspects of F. hepatica biology within Berdychiv district belonging to the forest-steppe zone of Zhytomyr region. Material and Methods. The work was carried out during 2020–2021. Collections of mollusks from water bodieson the territory of Berdichevsky district of Zhytomyr region served as the material for the research. Their identification was carried out by conchological features. Conventional methods were used for the parasitological study of mollusks. In total, more than 2000 mollusks Lymnaea (Galba) spp. were examined. Sampling of water and mollusks was carried out from four pasture reservoirs. Results. The main intermediate host of F. hepatica is the mollusk L. (G.) subangulata in the territory of Berdychiv region; L. (G.) truncatulaplays a secondary role in the distribution of this trematode. It was noted that the carriers of F. hepatica partenites are mainly mollusks with a shell height of 4.0 to 8.2 mm. New data on the dynamics of infection of L. (G.) subangulata with the trematode F. hepatica was obtained. The dynamics of infestation of these mollusks with F. hepatica cercariae shows a stable uniform character in the form of a two-peak curve, with peaks in May (2.51 ± 0.88 %) and August (9.19 ± 1.78 %). The overall prevalence of L. (G.) subangulata invasion by fasciola cercariae in the studied water bodies in 2020 was significantly lower than in 2021. Conclusions. In modern climatic conditions, in the territory of the region, permanent water bodies have become fasciolosis foci and common places for the settlement of L. (G.) subangulata, infected with F. hepatica cercariae. The most favorable environmental conditions for fasciola and its intermediate hosts develop in spring; accordingly; for the definitive hosts, this period is quite dangerous in terms of infection of animals.